Síntese e caracterização do cristal ternário de 1,10- fenantrolina e l-valina complexado com cobre (ii) para o uso como antitumorais - OLIVEIRA, Rayssa Rafaella de Souza da Cruz (2021)
Metal complexes have been notorious in the scientific community; complexes with transition metals such as copper have shown impressive results due to their significant pharmacological properties, especially in cancer treatment. This neoplasm has been a global problem since it has been the pathology in most frequent causes of deaths; in addition, many antitumor agents are losing their effectiveness due to the complexity of the tumors and the high resistance of the human organism to drugs. In this context, this research aims to synthesize and study the physicochemical and biological properties of the ternary crystal of 1.10-phenanthroline and l valine complexed copper (II) aiming its application in antitumor activity. The crystalline solid was synthesized by a slow evaporation solvent method for 15 days. The crystal was characterized by X-ray diffraction (XRD) with Rietveld refinement, Visible Ultraviolet Region (UV-Vis), Fourier Transform Infrared Spectroscopy (FT-IR), Raman Spectroscopy, Thermogravimetric Analysis (TG), Differential Thermal Analysis (DTA), Differential Scanning Calorimetry (DSC), solubility test and in vitro antitumor activity evaluation. According to the UV-Vis optical analysis, the ideal pH for crystallization of the sample is 8.98. Through XRD at room temperature (25° C / 298 K), the monocrystal has a triclinic structure with a space group P1, containing 2 molecules per unit cell (Z = 2) and lattice parameters: a = 7.173 (4) Å, b = 11.967 (9) Å and c = 12.279 (1) Å and the angles α = 68.290 (8) °, β = 77.810 (8) ° and γ = 83.661 (7) °. FT-IR and Raman spectra reveal Cu2+ ion complexation with the organic molecules. The thermoanalytical techniques showed that the phase transformation occurs between 50ºC to 70ºC through the dehydration of the material. The XRD as a function of temperature (27ºC to 232ºC) proved that the phase transformation of the material from the hydrated form to the anhydrous form is irreversible. The Le Bail method was used to refine the structure, which enabled the structural determination of this new phase, the lattice parameters: a = 12,379 (9) Å, b = 11,513 (8) Å, c = 7,039 (5) Å, α = 93,678 (1) º, β = 108,598 (2) º, γ = 111,767 (1) º °, and P1 triclinic structure. The solubility profile of the ternary crystal proved to be suitable for materials with anti-tumor properties, reaching 14,960 mg/ml in 240 min. The antitumor activity of the complex of 1.10-Phenanthroline and L-valine complexed Copper (II) was confirmed by means of cytotoxic tests using the tumor cell line PC-3. It showed IC50 = 2.7 μM, better result compared to the Docetaxel antineoplastic agent (IC50 = 4.38 μM).